Beyond the verbal: Pregnant women's preferences for receiving influenza and Tdap vaccine information from their obstetric care providers - Mallory Ellingson; Allison T. Chamberlain (Taylor & Francis Group, 2018)
Objective: Prenatal providers are pregnant women's most trusted sources of health information, and a provider's recommendation is a strong predictor of maternal vaccine receipt. However, other ways women prefer receiving vaccine-related information from prenatal providers, aside from face-to-face conversations, is unclear. This study explores what secondary communication methods are preferred for receiving maternal vaccine-related information. Study design: Obstetric patients at four prenatal clinics around Atlanta, Georgia received a 27-item survey between May 5th, 2016 and June 15th, 2016. Participants were asked about sources they currently use to obtain prenatal health information and their preferences for receiving vaccine-related information from providers. Descriptive statistics were calculated and chi-square tests were used to evaluate associations between participant characteristics and outcomes. Results: Women primarily reported using the CDC website (57.7%) and pregnancy-related websites (53.0%) to obtain vaccine information. Apart from clinical conversations, educational brochures (64.9%) and e-mails (54.7%) were the preferred methods of receiving vaccine information from providers, followed by their provider's practice website (42.1%). Communication preferences and interest in maternal immunization varied by race/ethnicity, age and education; white women were twice as likely to want information on a provider's practice website compared to African-American women (OR = 2.06; 95% CI: 1.31, 3.25). Conclusions: Pregnant women use the Internet for information about vaccines, but they still value input from their providers. While e-mails and brochures were the preferred secondary modes of receiving information, a provider's existing practice website offers a potential communications medium that capitalizes on women's information seeking behaviors and preferences while limiting burden on providers.